Unionisation Structures and Innovation Incentives - Christian Wey; Justus Haucap (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper examines how different unionisation structures affect firms' innovation incen- tives and industry employment. We distinguish three modes of unionisation with increasing degree of centralisation: (1) "Decentralisation" where wages are determined independently at the firm-level, (2) "coordination" where one industry union sets individual wages for all firms, and (3) "centralisation" where an industry union sets a uniform wage rate for all firms. While firms'investment incentives are largest under "centralisation," investment incentives are non-monotone in the degree of centralisation: "Decentralisation" carries higher investment incentives than "coordination". Labour market policy can spur innovation by decentralising unionisation structures or through non-discrimination rules.
Keywords: 330; Duopol; Tarifpolitik; Lohnverhandlungstheorie; Investition; Arbeitsproduktivität; Innovation; Theorie